2012
DOI: 10.1177/0165025412440947
|View full text |Cite
|
Sign up to set email alerts
|

I-states-as-objects-analysis (ISOA): Extensions of an approach to studying short-term developmental processes by analyzing typical patterns

Abstract: I-states-as-objects-analysis (ISOA) is a person-oriented methodology for studying short-term developmental stability and change in patterns of variable values. ISOA is based on longitudinal data with the same set of variables measured at all measurement occasions. A key concept is the i-state, defined as a person’s pattern of variable values at a specific time point. All i-states are first subjected to a classification analysis that results in a time-invariant classification characterized by a number of typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…To test the assumption of over-time structural invariance, we compared the squared Euclidian distance of the centroids from the ISOA solution to the time 1 centroids from the Ward’s clustering procedure. Distances less than 0.25 are considered acceptable (Bergman, Nurmi, von Eye & 2012). The mean distance between the solutions was 0.06, confirming the assumption of over-time structural invariance and indicating the appropriate use of ISOA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To test the assumption of over-time structural invariance, we compared the squared Euclidian distance of the centroids from the ISOA solution to the time 1 centroids from the Ward’s clustering procedure. Distances less than 0.25 are considered acceptable (Bergman, Nurmi, von Eye & 2012). The mean distance between the solutions was 0.06, confirming the assumption of over-time structural invariance and indicating the appropriate use of ISOA.…”
Section: Resultsmentioning
confidence: 99%
“…The squared Euclidian distance of the centroids obtained from the Study 1 cluster solution were compared to those from the Study 2 cluster solution to quantify the similarity of the friendship clusters. Distances should be less than 2 to be considered comparable (Bergman, Nurmi, & von Eye, 2012). …”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…According to a systematic review the TPB has helped the health sciences to explain and predict several healthcare provider behaviours (Godin, Belanger‐Gravel, Eccles, & Grimshaw, ) and clearly offers the investigators a theoretically sound framework for these purposes. Regarding the nursing profession, the TPB gives a good explanation of some nurses' behaviours, such as the correct measurement of blood pressure (Nelson, Cook, & Ingram, ), the reporting of suspected child abuse (Bergman, Nurmi, & Alexander, ) and the reporting of adverse drug reactions (Angelis et al., ). Prior studies have already found that attitudes towards the use of ND influences ND use in clinical practice (D'Agostino et al., ; de Souza Guedes et al., ; Romero‐Sanchez et al., ), however, it is noted that none of these studies considered behavioural, normative and control beliefs about ND use.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, structural and individual stability and change can be studied at the pattern level. Another method is I-States as Objects Analysis -ISOA (Bergman, Nurmi, & von Eye, 2012). In ISOA, shortterm development in a set of variables is studied by first finding a timeinvariant classification system, usually by employing cluster analysis.…”
Section: Exploratory Classification Analysis Based On Patterns Of Infmentioning
confidence: 99%